Study of natural background radiation in Kathmandu Valley - Pantha, Parkash; Bhusal, Tanka Prasad; Shah, Budha Ram; Koirala, Rajendra Prasad (BIBECHANA, 2018)
The study of natural background radiation dose at thirty two locations of Kathmandu valley has been done successfully using the instrument Radalert 100. The average dose rates and annual effective dose were measured. From the measurements, the least value of average dose rate was found to be (22.3±3.9)×10-3 mR/hr for Sundhara and the greatest value of average dose rate was  found to be (37.7±7)×10-3 mR/hr for Budhanilkantha 3.  As per the annual effective dose, the least value was 0.391 mSv/yr for Sundhara and the greatest value was 0.661 mSv/yr for Budhanilkantha 3. The average annual effective dose of Kathmandu valley was 0.475 mSv/yr ranging from 0.391 mSv/yr to 0.661 mSv/yr. The values thus obtained were compared to the worldwide average value of annual effective dose, 0.48 mSv/yr. Also, the obtained values were compared to the legal dose limit (annual effective dose), 1 mSv/yr set by International Commission on Radiological Protection (ICRP) for non-radiation workers and members of public. Among these thirty two locations, eight locations were chosen such that they had larger range of the observed dose rates. Those eight locations were re-observed. Further, Chi-square test was carried out to test whether the observed dose rates were following normal distribution or not. From the calculation, it was observed that the observed dose rates were following the normal distribution.BIBECHANA 16 (2019) 187-195